2006
DOI: 10.1242/dev.02555
|View full text |Cite
|
Sign up to set email alerts
|

General and cell-type specific mechanisms target TRPP2/PKD-2 to cilia

Abstract: Ciliary localization of the transient receptor potential polycystin 2 channel (TRPP2/PKD-2) is evolutionarily conserved, but how TRPP2 is targeted to cilia is not known. In this study, we characterize the motility and localization of PKD-2, a TRPP2 homolog, in C. elegans sensory neurons. We demonstrate that GFP-tagged PKD-2 moves bidirectionally in the dendritic compartment. Furthermore, we show a requirement for different molecules in regulating the ciliary localization of PKD-2. PKD-2 is directed to moving d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
129
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(146 citation statements)
references
References 81 publications
16
129
1
Order By: Relevance
“…A conclusion both from this work, as well as from previous studies, is that C. elegans sensory neurons do not appear to contain a mechanism that acts generally and broadly to sort all cilia-destined membrane proteins (e.g., Bae et al 2006;Wojtyniak et al 2013). For instance, although the DAF-25 Ankmy2 protein regulates ciliary localization of all GPCRs examined in this work, previous studies have shown that mutations in daf-25 affect localization of only a subset of other ciliary membrane proteins, including GPCRs, in different cell types (Fujiwara et al 2010;Wojtyniak et al 2013).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…A conclusion both from this work, as well as from previous studies, is that C. elegans sensory neurons do not appear to contain a mechanism that acts generally and broadly to sort all cilia-destined membrane proteins (e.g., Bae et al 2006;Wojtyniak et al 2013). For instance, although the DAF-25 Ankmy2 protein regulates ciliary localization of all GPCRs examined in this work, previous studies have shown that mutations in daf-25 affect localization of only a subset of other ciliary membrane proteins, including GPCRs, in different cell types (Fujiwara et al 2010;Wojtyniak et al 2013).…”
Section: Discussionmentioning
confidence: 49%
“…The clathrin adaptor AP-1 complex has been suggested to act broadly to retrieve cilia-targeted membrane proteins from a default trafficking pathway that would otherwise sort these proteins to the general cellular membrane compartment . Indeed, in AP-1 complex mutants, multiple ciliary membrane proteins including channels and GPCRs are mistargeted to the nonciliary plasma membrane Bae et al 2006;Kaplan et al 2010). However, our results indicate that the AP-1 complex acts in a protein-and cell-specific manner to target GPCRs to cilia such that localization of STR-44, but not STR-163, to AWB cilia is affected in unc-101 mutants, whereas UNC-101 is required for ciliary localization of both STR-163 and SRBC-64 in ASK.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the localization of these proteins was essentially undisturbed in ciliary tubulin mutants, consistent with the idea that TBA-6, TBA-9, and TBB-4 are more important for specialized cilium functions than for general aspects of ciliogenesis. In contrast, previous work in C. elegans has shown that cell type-specific factors, including the kinesinlike protein KLP-6, are important for the proper transport of signaling molecules in particular types of ciliated neurons (Peden and Barr 2005;Bae et al 2006;Jauregui et al 2008;Bae et al 2009). Here, we find that some specialized cilia, especially those of the CEM neurons, are particularly dependent on tba-6 and tbb-4 function.…”
Section: Discussionmentioning
confidence: 79%
“…14 Transport of polycystins to the primary cilium is tightly regulated and several mediators of different trafficking steps have been identified to direct vesicles to the primary cilium base. 3,[15][16][17] In this region, known as basal body, a selective barrier regulates entry of specific proteins inside the ciliary compartment. 18,19 A key player in this selective entry of ciliary components is the small guanosine triphosphatase (GTPase) Rab8.…”
mentioning
confidence: 99%